Chimerism evaluation in measurable residual disease‐suspected cells isolated by flow cell sorting as a reliable tool for measurable residual disease verification in acute leukemia patients after allogeneic hematopoietic stem cell transplantation. Issue 5 (28th December 2020) - Semchenkova, Alexandra; Brilliantova, Varvara; Shelikhova, Larisa; Zhogov, Vladimir; Illarionova, Olga; Mikhailova, Ekaterina; Raykina, Elena; Skorobogatova, Elena; Novichkova, Galina; Maschan, Alexey; Maschan, Michael; Popov, Alexander
Abstract: Background: The presence of minimal/measurable residual disease (MRD) before or after hematopoietic stem cell transplantation (HSCT) is known as a predictor of poor outcome in patients with acute myeloid (AML) or lymphoblastic (ALL) leukemia. When performed with multiparameter flow cytometry (MFC), assessment of residual leukemic cells after HSCT may be limited by therapy‐induced shifts in the immunophenotype (e.g., loss of surface molecules used for therapeutic targeting). However, in such cases, questionable cells can be isolated and tested for hematopoietic chimerism to clarify their origin. Methods: Questionable cell populations were detected during the MFC‐based MRD monitoring of 52 follow‐up bone marrow samples from 37 patients diagnosed with T cell neoplasms ( n  =14), B cell precursor ALL ( n  = 16), AML ( n  = 7). These cells (suspected leukemic or normal) were isolated by flow cell sorting and tested for hematopoietic chimerism by RTQ‐PCR. Results: The origin of cells was successfully identified in 96.15% of cases ( n  = 50), which helped to validate the results of MFC‐based MRD monitoring. Conclusions: We believe that a combination of MFC, cell sorting, and chimerism testing may help confirm or disprove MRD presence in complicated cases after HSCT.